What has changed? The impact of Covid pandemic on the technology and innovation management research agenda - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2020)
Whereas the pandemic has tested the agility and resilience of organizations, it forces a deeper look at the assumptions underlying theoretical frameworks that guide managerial decisions and organizational practices. In this commentary, we explore the impact of the Covid‐19 pandemic on technology and innovation management research. We identify key assumptions, and then discuss how new areas of investigation emerge based on the changed reality.